Empowering Communities through the Living Qur’an: Alumni Contributions from a Qur’anic Boarding School in Indonesia - Ahmad Muttaqin; M. Achlami H.S.; Ahmad Isnaeni; Khairullah Khairullah (UIN Sunan Gunung Djati Bandung, 2026)
This study explores how the alumni of the Raudhatul Qur’an Islamic Boarding School in Metro City contribute to community empowerment through the Living Qur’an framework. The research aims to examine the effectiveness of alumni-led initiatives in sustaining religious knowledge and practices in a city undergoing cultural and religious transitions. Using a qualitative-descriptive approach and a case study method, data were collected through in-depth interviews with alumni and pesantren caregivers, as well as documentation of institutional and community activities. The analysis employs Jim Ife’s community development theory and Robert D. Putnam’s social capital theory to assess how alumni utilize social trust, norms, and networks to promote Quranic values within society. The findings reveal a distinct model of Living Qur’an-based community empowerment implemented through three main strategies: active community participation, social justice, and local capacity building. The study concludes that the alumni effectively preserve and revitalize Quranic culture by leveraging their social capital, reinforcing the potential of religious institutions as drivers of community development in urban transitional contexts. This research contributes to the discourse on Islamic education, social cohesion, and faith-based community empowerment in contemporary urban settings.